Effect of Ferrite Bead on Honda Suprafit 100 CC Engine Performance - Makinun, Makinun; Masruri, Thohir; Fauzi, Agus Muhammad; Rastoto, Nur Dyan Enggar (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
Ferrite beads, ceramic compounds made from iron oxide powder, have been shown to enhance the performance of gasoline engines using premium fuel, pertalite, and pertamax. This research demonstrated that installing ferrite beads in the ignition system of gasoline engines led to improvements in power, torque, acceleration time, and the efficiency of the spark plug ignition system. These findings suggest that ferrite beads can boost engine performance without compromising the quality of the combustion process.